2020
DOI: 10.1016/j.biomaterials.2020.120189
|View full text |Cite
|
Sign up to set email alerts
|

Towards systems tissue engineering: Elucidating the dynamics, spatial coordination, and individual cells driving emergent behaviors

Abstract: Biomaterial systems have enabled the in vitro production of complex, emergent tissue behaviors that were not possible with conventional two-dimensional culture systems, allowing for analysis of both normal development and disease processes. We propose that the path towards developing the design parameters for biomaterial systems lies with identifying the molecular drivers of emergent behavior through leveraging technological advances in systems biology, including single cell omics, genetic engineering, and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 250 publications
(349 reference statements)
0
4
0
Order By: Relevance
“…[ 2 ] The spatial distribution of cells and interactions between neighboring cells in native microenvironments are of fundamental importance in determining cell fate, such as migration, proliferation, apoptosis, and differentiation. [ 3 ] Moreover, the intricate communication among these prepatterned cell populations also plays an essential role in the creation of tissue architecture, the development of organ function, and the maintenance of tissue homeostasis. [ 4 ] Mimicking the spatial arrangements of these cellular interactions in vitro may allow for the recapitulation of multiple biological processes involved in the formation of natural tissues, resulting in the attainment of higher‐order biological functions and collective behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] The spatial distribution of cells and interactions between neighboring cells in native microenvironments are of fundamental importance in determining cell fate, such as migration, proliferation, apoptosis, and differentiation. [ 3 ] Moreover, the intricate communication among these prepatterned cell populations also plays an essential role in the creation of tissue architecture, the development of organ function, and the maintenance of tissue homeostasis. [ 4 ] Mimicking the spatial arrangements of these cellular interactions in vitro may allow for the recapitulation of multiple biological processes involved in the formation of natural tissues, resulting in the attainment of higher‐order biological functions and collective behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these challenges are discussed later in this document, although the authors recommend a further study of the basic principles and state of the art of the abovementioned scientific fields. Detailed reviews focused on each of these research areas can be consulted elsewhere [33][34][35][36][37][38][39][40][41].…”
Section: Ooc Basic Featuresmentioning
confidence: 99%
“…Overcoming the individual challenges is the key for translating OoC to cost-effective and sustainable implementation. We briefly introduce some of those relevant challenges, however, more insight into each research area can be found on specific reviews developed for this purpose, which can be found elsewhere [33][34][35][36][37][38][39][40][41]137,138].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Tissue engineering (TE) is a field of regenerative medicine, which is aimed at the development and application of various methods and principles of scientific areas such as biology, materials science, nanotechnology and medicine, allowing to obtain biological surrogates for the restoration or replacement of damaged areas of human organs or tissues [1][2][3]. Despite the active development of TE in the last few decades, some problems remain unsolved, namely: the high cost of an artificial organ growing [4]; difficult achievement of cell distribution with high density [5] and spatial position accuracy [6]; as well as the achievement of oriented growth of blood vessels [7].…”
Section: Introductionmentioning
confidence: 99%